Heterogeneity in the seroprevalence of hepatitis E virus among hospital attendees: a retrospective study in Shanghai, China - Lu, Jie; Li, Qing; Zhang, Chenxi; Li, Ziqiang; Guo, Qing; Cao, Zhujun; Yao, Yu-Feng; Xie, Qing (Infectious diseases (London, England), 2025)
Hepatitis E virus (HEV) infection is endemic in China. However, there are scarce data of HEV infection among hospital attendees seeking medical treatment or examination for various reasons. We aim to investigate the prevalence and incidence of HEV infection by time, age, sex, and across departments in a tertiary hospital. Paired results of anti-HEV immunoglobulin G (IgG) and IgM of 31,181 unique subjects during 2021-2022 were analysed. Overall seropositivity (95% confidence interval) of anti-HEV IgG and IgM was 41.25% (40.71%-41.80%) and 2.35% (2.19%-2.53%), respectively. Acute hepatitis E was more prevalent during winter-early spring and among adults aged 31-70. Anti-HEV IgG seroprevalence increased with age, levelling off at > 60 years of age. Not only the seropositivity, but also the levels of anti-HEV IgG were significantly lower in women than men of middle and old age. Young patients from the Department of Neurology had a significantly higher ratio of past HEV infection, while patients with manifestations of hepatitis, gastrointestinal symptoms or hematological diseases had higher seropositivity of anti-HEVIgM and should have high priority to HEV screening. Heterogeneity of HEV seroprevalence was noted at different times of the year, between sexes, among age groups and across departments in general hospital. The concentration of HEV-infected patients in a few departments supports a more focused screening strategy in health-care settings.